Analysis of Lexical and Grammatical Meaning in the Song “Alamak” by Rizky Febian (Semantic Study) - Sulastri, Saptiana; Ayu, Centika; Anisa, Elegia; Uri, Marsiana; Hairatunisa, Syarifah (Jurnal Bahasa Indonesia Prima (BIP), 2026)
Semantics is a branch of linguistics that studies the meanings and relationships among language units, such as words, phrases, clauses, and sentences. This study aims to analyze the lexical and grammatical meanings in the lyrics of the song "Alamak" by Rizky Febian. The study uses a qualitative descriptive approach with text analysis. Data in the form of words, phrases, and sentences in the song lyrics were collected through listening and note-taking, and literature studies, then analyzed using semantic theory. The results of the study show that lexical meaning is evident in words such as "cinta" and "rindu," which have basic meanings, while grammatical meaning emerges through affixation and sentence structure, as in the phrase "terlalu cinta," which conveys intensity. These findings indicate that the combination of lexical and grammatical meanings strengthens the emotional message in the song lyrics.